Developers Talking About Code Quality: study design and dataset - Jürgen Börstler (Blekinge Institute of Technology, 2023)
Electronic supplement for the article Developers Talking About Code Quality

Please refer to the following paper when you cite/use this data:

J. Börstler, K.E. Bennin, S. Hooshangi, J. Jeuring, H. Keuning, C. Kleiner, B. MacKellar, R. Duran, H. Störrle, D. Toll, J van Assema. Developers Talking About Code Quality. Empirical Software Engineering, 2023.
https://link.springer.com/article/10.1007/s10664-023-10381-0

Overview of the electronic supplement (sorted according to file names)


The data



data_all-except-Q4.xlsx
The original cleaned data for Questions Q1-Q3 and Q5-Q11.

data_Q4 assertions.xlsx
The "assertions" which are based on the transcripts of Q4.



The information provided to study participants



participants_consent-form_EN.pdf
The consent form the participants signed (English version, interviewees received a copy on request).

participants_interview-info.pdf
The information sheet that was handed out for recruiting interview participants (they could keep this form).



The study design and guidelines



study-design_coding-guide_birds-eye-summaries.pdf
The guidelines for coding the transcripts of Q4 into "assertions" (which we call "birds-eye summaries" in these guidelines).

study-design_main.pdf
The main study guide comprising (among others) a detailed interview script.

study-design_transcription.pdf
The guidelines used for transcribing Q4.
Keywords: Computer and Information Sciences; Data- och informationsvetenskap (datateknik)